Performance analyses and optimisation of the Joule-Brayton cycle via the mean cycle pressure criterion - Karakurt, A. Sinan; Sahin, Bahri (INDERSCIENCE ENTERPRISES LTD, 2018)
Within the scope of developing a new method to optimise the use of economic and ecological thermal systems, a comparative study was conducted by means of different compression ratios and temperature ratios according to mean cycle pressure (MCP) criterion for the simple Joule-Brayton cycle. The results, when compared with the other performance criteria's results in the literature, show that the thermal efficiency and network at maximum MCP condition are approximately 1-2% more and 12-13% times less than other criteria, respectively. Moreover, the thermal efficiency that corresponds to the maximum MCP condition is nearly 15% more than the maximum network condition, and the network at the maximum MCP and maximum thermal efficiency conditions are equal. Thus, MCP criterion will give more useful and realistic information in terms of designing more efficient and smaller thermal systems.
Keywords: exergy density; Joule-Brayton cycle; MCP; mean cycle pressure; MAXIMUM POWER; EFFICIENCY; ENGINE; OUTPUT; Thermodynamics; Energy & Fuels